Geophysics in engineering investigations - McDowell, P. W. (Geological Society engineering geology special publication, 2002)
The full potential of geophysics in engineering investigations is still to be realised. The many available techniques can provide important information about the ground, its mass properties, its small-scale variations, and its anomalies of structure or content. The advantage of a geophysical survey is that it enables information to be obtained for large volumes of ground that cannot be investigated by direct methods due to cost. The applications of geophysics in the characterisation Of contaminated land are still developing, but have great potential for example in the distribution and migration of pollutants in the ground and groundwater. Geophysics is still insufficiently or inappropriately used in engineering and the newer capabilities are not appreciated. This report is published in co-operation with the Geological Society and presents a logical guide through the process of using geophysical investigation methods in site characterisation. It explores the roles of geophysical, methods and, provides the back.ground to geophysics as an investigative tool. The procurement, management and reporting frameworks for a geophysical investigation are set out and the underlying science and current practices of the main techniques are explained, as well as the processes of data acquisition, handling and presentation. The different targets determinable by geophysical methods are considered in separate sections for geological, geotechnical, geo-environmental and structural engineering applications. The report concludes with recommendations for practice. --